Relative effectiveness of Google classroom and WhatsApp in enhancing biology interest among Nigerian university students - Okoli, Josephine Nwanneka; Ukala, Geoffrey (Univeritas Papua, 2025)
This study compares the effectiveness of Google Classroom and WhatsApp in enhancing biology interest among university students in southeast Nigeria. A quasi-experimental, specific, non-randomized pre-test and post-test compare group design was used. The population comprised 252-year undergraduate biology education students from the five Federal Universities in South-East Nigeria, out of which 118 (70 male and 182 female) students were purposively sampled from two universities. The instrument used for data collection was the Biology Interest Inventory (BII). Mean and standard deviation were used to address the research questions, whereas ANCOVA was utilized to evaluate the hypothesis. Results showed that students instructed using Google Classroom instruction had higher mean interest scores than their counterparts taught using WhatsApp instruction. Although female students were found to have slightly higher interest than males on the test of significance, gender was found not to have a significant influence on students' mean interest scores. Implying that both instructions enhance students' interest irrespective of gender. Similarly, no interaction effect of instructional strategies and gender on students' interest in basic biology was found. It was recommended that training programs should be implemented to ensure both students and instructors are proficient in using these platforms to their full potential.